PERBANDINGAN KARAKTER ANATOMI BATANG BEBERAPA JENIS BAMBU DI HUTAN CAGAR ALAM LEMBAH ANAI - Azri, Harizqi; Maideliza, Tesri; Meriko, Lince (STKIP PGRI Sumbar, 2013)
ABSTRACTBamboo distributed in various places in West Sumatera, including at Anai Valley Nature Reserve Tanah Datar District. Anai Valley Nature Reserve has a high biodiversity that estimated diversity at Anai Valley is quite high. Descriptions using the bamboo flower organs was difficult because most rare bamboo flowering and some have not flowering. It is necessary to look for other alternatives as descriptions of materials, namely by using the anatomical structure of vegetative organs such as culm. To determine the type of bamboo that is at Anai Valley Nature Reserve has conducted investigated on morphological and anatomical characters some of bamboo species, using descriptive and quantitative methods were conducted in March-July 2013. Specimens of bamboo identified in Herbarium Andalas University (ANDA) Padang. Making preparations carried out in the Laboratory of Structural Plant Development, Department of Biology, Andalas University, Padang. Results of present study, six species of bamboo in Anai Valley Nature Reserve are: Bambusa balcooa (Roxb.) Voigt, Schizostachyum brachycladum Kurz, Bambusa glaucophylla Widjaja, Schizostachyum silicatum Widjaja, Bambusa vulgaris Schrad. Ex Wendl, Schizostachyum mampouw. Anatomical culm structure of B.balcooa, B.glaucophylla. and B.vulgaris, tends to have a dominant fiber outer sheath compared with Schizostachyum genus. Genus Bambusa consists of 6-9 rows that have a separate fiber sheath of vascular bundle centripetally, while the genus Schizostachyum obtained 3-4 rows. Longest fiber in Bambusa vulgaris get on that 2830±32 mm and the shortest on Bambusa glaucophylla is 1855±20 mm . While the width of the fiber diameter on Scyzostachyum silicatum at 28±4 mm and narrowest on Bambusa vulgaris is 19±4 mm. Comparison perenkim cell diameter of the rod toward the edge of the shows that growth stems from the edges toward the inside